2015
DOI: 10.1039/c5ra19816j
|View full text |Cite
|
Sign up to set email alerts
|

A promising broadband and thin microwave absorber based on ternary FeNi@C@polyaniline nanocomposites

Abstract: Ternary FeNi@C@polyaniline (PANI) nanocomposites are synthesized by combining the arc-discharge process and an in situ chemical oxidative polymerization reaction, and can be seen as a good candidate for microwave absorbents with a broad bandwidth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Due to the high density of magnetic ferrites/metals, the improvements in EM properties by constantly accumulating magnetic components will be contrary to the requirements of practical applications, and thus employment of another dielectric medium becomes a more prospective mode that can maintain the specific gravity of the composites within the acceptable level. Generally, this kind of multi-compound CP-based composite is constructed on the basis of a simple magnetic composite, and the CPs will act as a shell layer and organic binder [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. For example, Han et al prepared FeNi@C@PANI nanocomposite by combining the arc-discharge process and an in situ chemical polymerization reaction.…”
Section: Cp-based Composites As Mamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high density of magnetic ferrites/metals, the improvements in EM properties by constantly accumulating magnetic components will be contrary to the requirements of practical applications, and thus employment of another dielectric medium becomes a more prospective mode that can maintain the specific gravity of the composites within the acceptable level. Generally, this kind of multi-compound CP-based composite is constructed on the basis of a simple magnetic composite, and the CPs will act as a shell layer and organic binder [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. For example, Han et al prepared FeNi@C@PANI nanocomposite by combining the arc-discharge process and an in situ chemical polymerization reaction.…”
Section: Cp-based Composites As Mamsmentioning
confidence: 99%
“…It was found that the introduction of PANI could enhance the relative complex permittivity to some extent, and pull down the density of the composite effectively. Compared with FeNi@C, the FeNi@C@PANI nanocomposite could perform similar microwave absorption with thinner absorber thickness [ 152 ]. Yang et al also confirmed that a PPy-encapsulated nickel-coated graphite nanosheet had much better microwave absorption properties than a binary nickel-coated graphite nanosheet and a PPy-coated graphite nanosheet [ 155 ].…”
Section: Cp-based Composites As Mamsmentioning
confidence: 99%
“…The extra slight peak of CNF-6 sample is mainly associated with the additional interfaces between FeNi and carbon. 39,40 As we can see, complex permittivity becomes higher when carbonized time has been increased from 1 to 6 h. Nevertheless, compared with CNF-4 and CNF-6 samples, it is found that CNF-12 sample exhibit lower complex permittivity and higher complex permeability, which could be resulted from the destruction of 1D carbon nanofibers structure. 41 As can be seen in Figure 6c, these samples exhibit similar and lower relative complex permeability curves, which are related to the smaller magnetization.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Fe, Co, Ni, and their alloys exhibit high magnetization and low coercivity and find applications in the EMI shielding. 7 Han et al 14 reported that nickel is suitable for microwave absorption at high frequency over gigahertz owing to the higher Snoek's limit. In this context, very limited work has been reported on RGO/Ni and RGO/Ni/polyaniline composites.…”
Section: ■ Introductionmentioning
confidence: 99%